2018
DOI: 10.1093/aobpla/ply018
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and germination vary within and among species of milkweeds

Abstract: Declines in pollinator populations and monarch butterflies require restoration of habitats with the plants and floral resources that support them. Monarch butterflies in particular lay their eggs exclusively on milkweed species, which their caterpillars require as a food source. Restoring populations of milkweeds can involve planting plugs grown from seed, but recommendations for breaking dormancy and germinating milkweed seeds often disagree. We tested the hypothesis that seed germination and dormancy vary wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…A. curassavica does not require a germination treatment to break seed dormancy, whereas A. syriaca requires an extended seed dormancy period (of a year or more) combined with cold stratification before a germination rate of 50% or more can be achieved (Baskin and Baskin, 1977;Groh, 1943). A. fascicularis requires 4 to 6 weeks of stratification to break dormancy, and A. speciosa requires, on average, 2 to 4 weeks of stratification (Kaye et al, 2018). As hybrid parents varied in germination requirements, the two most common germination methods of DS and stratification were used to determine the optimal germination method.…”
Section: Resultsmentioning
confidence: 99%
“…A. curassavica does not require a germination treatment to break seed dormancy, whereas A. syriaca requires an extended seed dormancy period (of a year or more) combined with cold stratification before a germination rate of 50% or more can be achieved (Baskin and Baskin, 1977;Groh, 1943). A. fascicularis requires 4 to 6 weeks of stratification to break dormancy, and A. speciosa requires, on average, 2 to 4 weeks of stratification (Kaye et al, 2018). As hybrid parents varied in germination requirements, the two most common germination methods of DS and stratification were used to determine the optimal germination method.…”
Section: Resultsmentioning
confidence: 99%
“…Seeds are wind‐dispersed and most are conditionally dormant at maturity; dormancy declines during after‐ripening and especially after a period of cold‐moist stratification (Baskin & Baskin 1977; Finch et al 2018). No studies have identified persistent seed banks for milkweed species (Johnson & Anderson 1986; Csontos et al 2009; Kaye et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Se utilizaron cinco repeticiones de 100 semillas cada una; se colocaron a germinar en toallas de papel humedecidas con agua destilada en una cantidad equivalente a 2,5 veces la masa del sustrato seco (Carvalho et al, 2013;Macedo et al, 2017;Oliveira et al, 2018), en un recipiente plástico previamente desinfectado, en condiciones de oscuridad durante 72 horas (Salazar & Botello, 2018). Fueron consideradas semillas germinadas aquellas que presentaron la radícula de al menos tres milímetros de largo (Kaye et al, 2018), y se expresó como porcentaje de germinación.…”
Section: Prueba De Germinaciónunclassified